The roles of helix I and strand 5A in the folding, function and misfolding of α1-antitrypsin. - Anja S Knaupp (Public Library of Science (PLoS), 2013)
α(1)-Antitrypsin, the archetypal member of the serpin superfamily, is a metastable protein prone to polymerization when exposed to stressors such as elevated temperature, low denaturant concentrations or through the presence of deleterious mutations which, in a physiological context, are often associated with disease. Experimental evidence suggests that α(1)-Antitrypsin can polymerize via several alternative mechanisms in vitro. In these polymerization mechanisms different parts of the molecule are proposed to undergo conformational change. Both strand 5 and helix I are proposed to adopt different conformations when forming the various polymers, and possess a number of highly conserved residues however their role in the folding and misfolding of α(1)-Antitrypsin has never been examined. We have therefore created a range of α(1)Antitypsin variants in order to explore the role of these conserved residues in serpin folding, misfolding, stability and function. Our data suggest that key residues in helix I mediate efficient folding from the folding intermediate and residues in strand 5A ensure native state stability in order to prevent misfolding. Additionally, our data indicate that helix I is involved in the inhibitory process and that both structural elements undergo differing conformational rearrangements during unfolding and misfolding. These findings suggest that the ability of α(1)-Antitrypsin to adopt different types of polymers under different denaturing conditions may be due to subtle conformational differences in the transiently populated structures adopted prior to the I and M* states.